A rare case of fatal stroke after ethylene glycol toxicity. (25th March 2015) - Garg, Deepika; Lim, Tanna; Irani, Mohamad
Abstract : A 58-year-old man presented to the emergency department with acute left-sided weakness and left visual field defect. His examination was significant for confusion, acetone odour, tachycardia and tachypnoea. Further blood tests revealed an anion gap of 31 mEq/L, serum osmolal gap of 34 mOsm/kg, and creatinine 3.6 mg/dL. Brain MRI revealed acute infarctions scattered throughout the brain along with generalised oedema. The patient deteriorated rapidly and soon thereafter it was reported that a bottle of antifreeze was found near him at home. Haemodialysis was initiated and the patient received fomepizole and bicarbonate. Three days later the patient did not show any neurological improvement and expired later that day. Ethylene glycol toxicity can rarely present with stroke which can be life-threatening when not diagnosed and managed in a timely fashion.